(untitled) (Revista Puertorriqueña de Psicologia, 2016)
Social support has been established as an important factor for health maintenance and general well-being. In Puerto Rico, research has neglected to explore this subject among HIV-Discordant couples. Our study aimed to explore the perceived role of social support within HIV-Discordant couples, specifically its perceived impact on safer sexual practices and adherence to treatment. We implemented an exploratory and transversal qualitative design, and we carried out in-depth interviews with 20 heterosexual HIV-Discordant couples (n=40). Results highlight the important role that social support plays on adherence to treatment and condom use while also documenting the challenges faced in providing and receiving that support. Recommendations for future research and intervention development are provided.